Robotic nipple-sparing mastectomy for cancer risk reduction: demonstration of applicability and surgical results - Bernardi, Rodrigo; Linhares, José Clemente; Tsunoda, Audrey; Hatschbach, Sérgio Bruno Bonatto; Ribeiro, Reitan; Groth, Anne Karoline; Kruk, Isabeli Lopes (Brazilian Journal of Oncology, 2022)
Introduction: Robotic nipple sparing mastectomy (RNSM) may be a breakthrough for breast cancer risk reduction surgeries, providing better aesthetic results. This study aims to spread the knowledge of the robotic surgical technique, still little performed in the world, and to demonstrate the applicability and surgical results.Methods: RNSM was offered to patients with small or medium volume breasts, ptosis up to grade 2, and all with genetic mutations at increased risk for breast cancer. The Surgical System da Vinci Si® (Intuitive Surgical, Sunnyvale, CA) was used for the surgeries. The satisfaction of each patient and the time of the surgeries were evaluated.Results: A total of 4 patients underwent surgery, all of whom had genetic mutations that would make breast cancer prevalent. The duration of the surgery was drastically reduced from 6h20min to 3h in the last surgery. There were no serious complications, such as prosthesis loss or nipple necrosis. Skin burning was noted in two patients, with complete resolution over the weeks.Conclusion: RNSM has a fast-learning curve and excellent aesthetic results in patients who fit the criteria for surgery.
Keywords: Prophylactic mastectomy; Robotic surgical procedures; Breast neoplasms